Expression Profile Analysis of the Cell Cycle in Diploid and Tetraploid Carassius auratus red var. - Ren, Li; Lu, Jiahao; Fan, Yunpeng; Hu, Yibo; Li, Jiaming; Xiao, Yamei; Liu, Shaojun (Frontiers in Genetics, 2020)
Polyploidization often leads to ‘transcriptome shock’, and can create a new species. Analysis of the cell cycle, which is associated with survival in polyploidy, has proved useful in investigating polyploidization. Here, we used mRNA sequencing to investigate global expression in vitro (in cultured cells) and in vivo (in fin and liver tissues) in both the diploid and tetraploid state. Differential expression of genes in diploid (7482, 36.0%) and tetraploid (3787, 18.2%) states suggested that conditions in vitro and in vivo dramatically change mRNA expression levels. However, of the 20,771 total shared expressed genes, 18,050 (87.0%), including 17,905 (86.2%) non-differentially expressed genes (DEGs) and 145 (0.7%) DEGs between diploids and tetraploids, showed the same expression trends in both cultured cells and liver tissues. Of the DEGs, four of seven genes in the cell cycle pathway had the same expression trends (upregulated expression in diploids and tetraploids) in both cultured cells and liver tissues. Quantitative PCR analysis confirmed the same expression trends in the nine DEGs associated with regulation of the cell cycle, suggesting the existence of steady states in cell cycle-regulated genes. This research into common characteristics between diploids and tetraploids provides insights into the underlying molecular regulatory mechanisms of polyploidization. The steady changes that occur between diploids and tetraploids in vitro and in vivo show the potential value of studying polyploidy processes using cultured cell lines, especially with respect to cell cycle regulation.